Male Facial Appearance and Offspring Mortality in Two Traditional Societies. - Lynda G Boothroyd; Alan W Gray; Thomas N Headland; Ray T Uehara; David Waynforth; D Michael Burt; Nicholas Pound (PLoS ONE, 2017)
It has been hypothesised that facial traits such as masculinity and a healthy appearance may indicate heritable qualities in males (e.g. immunocompetence) and that, consequently, female preferences for such traits may function to increase offspring viability and health. However, the putative link between paternal facial features and offspring health has not previously been tested empirically in humans. Here we present data from two traditional societies with little or no access to modern medicine and family planning technologies. Data on offspring number and offspring survival were analysed for the Agta of the Philippines and the Maya of Belize, and archive facial photographs were assessed by observers for attractiveness and masculinity. While there was no association between attractiveness and offspring survival in either population, a quadratic relationship was observed between masculinity and offspring survival in both populations, such that intermediate levels of masculinity were associated with the lowest offspring mortality, with both high and low levels of masculinity being associated with increased mortality. Neither attractiveness nor masculinity were related to fertility (offspring number) in either population. We consider how these data may or may not reconcile with current theories of female preferences for masculinity in male faces and argue that further research and replication in other traditional societies should be a key priority for the field.